Relationship between body image and self-acceptance of female students - Siti Maryam; Ifdil Ifdil (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of female students who give a negative assessment of their body shape. The impact of the student is not being able to accept the situation that is in him. This study aims to examine the significant relationship between body image and self-acceptance of female students. This study uses quantitative methods with descriptive and correlation types. The total sample of 242 students was selected using a purpose stratified random sampling technique. The research instrument used was body image inventory and inventory of female student self-acceptance. Data were analyzed by Pearson Product Moment technique. The results revealed that there was a significant relationship between body image and self-acceptance of female students with a correlation coefficient of -0.469 which was at a significance level of 0,000. This can be interpreted that the more positive the body image, the higher the level of self-acceptance, and vice versa, the more negative the body image, the lower the level of self-acceptance. With the findings of these studies, counselors can provide guidance and counseling services such as information services, individual counseling services, group guidance services, and group counseling services specifically related to body image and self-acceptance.